2019
DOI: 10.1021/acsami.9b07100
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Derived Co3O4@NC with Core–Shell Structures for N2 Electrochemical Reduction under Ambient Conditions

Abstract: We report the development of MOF-derived nitrogen-doped carbon/ Co 3 O 4 nanocomposites (Co 3 O 4 @NCs) with core−shell structures as an efficient electrocatalyst for the artificial nitrogen fixation at room temperature and atmospheric pressure in 0.05 M H 2 SO 4 . It exhibits a high NH 3 yield of 42.58 μg h −1 mg cat.−1 and a faradaic efficiency of 8.5% at −0.2 V versus reversible hydrogen electrode. Experimental results show that the great N 2 reduction reaction performance of Co 3 O 4 @NCs originates from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 41 publications
(74 reference statements)
6
92
0
Order By: Relevance
“…First, "shell" acts as a protective layer to protect the core components from corrosion or dissolution when is composed of stable-state phases. [97][98][99] For example, Yang et al modified the gold core with metal-organic framework (MOF)-8 shell, which not only wrapped the gold core as a protective layer, but also regulated the diffusion layer near the surface of the gold core to promote the nitrogen fixation reaction. [98] Meanwhile, Peng et al found that the carbon layer in Fe 3 C@C heterostructure played a similar role in preventing the Fe 3 C core from being corroded during the catalytic process.…”
Section: Heterostructure Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…First, "shell" acts as a protective layer to protect the core components from corrosion or dissolution when is composed of stable-state phases. [97][98][99] For example, Yang et al modified the gold core with metal-organic framework (MOF)-8 shell, which not only wrapped the gold core as a protective layer, but also regulated the diffusion layer near the surface of the gold core to promote the nitrogen fixation reaction. [98] Meanwhile, Peng et al found that the carbon layer in Fe 3 C@C heterostructure played a similar role in preventing the Fe 3 C core from being corroded during the catalytic process.…”
Section: Heterostructure Engineeringmentioning
confidence: 99%
“…d) NH 3 yield and FE of Co 3 O 4 @NC‐10 at each given potential. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Heterostructure Engineeringmentioning
confidence: 99%
“…In addition, MOFs have attracted tremendous attention in the field of heterogeneous catalysis. [70] Five prototypical MOFs, Fe based-ZIF-8(Fe), [71] Co-based ZIF-67(Co), [72] PCN-222(Fe), [73] Cu II À MOF, [74] HKUST-1 (Cu-benzene-1,3,5-tricarboxylate) [75] were investigated, demonstrating the highest performance with NH 3 [76] Recently, Luo et al found that MOF-derived C@NiO@Ni microtubes (Figure 3a,3b) perform well in NRR, reaching both a high NH 3 yield rate of 43.15 μg h À 1 mg cat À 1 and a FE of 10.9% at À 0.7 V (Figure 3c). [77] The rich 3D interconnected porous structure of MOFs is conducive to the enrichment and diffusion of reactant nitrogen molecules, and a large number of atomic distribution metal ions as a Lewis acid in MOFs is considered as the active sites, which can withdraw p electrons from N 2 molecules and weaken the N � N bonds.…”
Section: Mof Based Catalystmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs), as an emerging category of porous materials, have attracted great interest due to their unique physicochemical properties, such as their highly specific surface area, tunable porosity, and controllable functionality (Liu et al, 2010 ; Aiyappa et al, 2019 ; Bhadra et al, 2019 ). Therefore, MOFs have been widely applied in various energy conversion and storage systems, such as gas separation and storage (Furukawa and Yaghi, 2009 ; Salehi and Anbia, 2017 ), drug delivery (Cai et al, 2019a , b ; Safaei et al, 2019 ), biosensors (Zhang et al, 2016 ; Qiu et al, 2019 ), heterogeneous catalysis, and CO 2 /N 2 conversion (An et al, 2017 ; Luo et al, 2019 ). However, because of their unsatisfactory electrical conductivity and stability, it greatly hinders their application in CO 2 reduction processes.…”
Section: Introductionmentioning
confidence: 99%